Fostering Cooperation Through Project-Based Learning: A Qualitative Investigation of Fifth-Grade Civics Education in Elementary Schools - Farhansyah, Fickry Nur; Putra, Nugraha Permana; Widiawati, Hema (Journal of Innovation and Research in Primary Education, 2025)
Project-Based Learning (PjBL) has gained recognition for fostering collaborative skills, yet limited research explores cooperation development mechanisms in elementary Civics Education contexts. This qualitative case study examined PjBL implementation and cooperation development among 28 fifth-grade students at SDN 1 Plumbon. Data were collected through structured classroom observations, semi-structured interviews with students and teacher, and documentation analysis. Data analysis employed Miles and Huberman's interactive model with triangulation to ensure validity. Findings revealed that cooperation developed progressively through four key mechanisms: equitable role distribution ensuring individual contributions, inclusive communication promoting equal participation, positive interdependence fostering collective responsibility, and collaborative conflict resolution facilitated by teacher mediation. Students demonstrated enhanced solidarity, democratic decision-making, and spontaneous helping behaviors. Teacher facilitation emerged as the most critical supporting factor, while time constraints presented manageable challenges that ultimately strengthened organizational skills. The classroom environment's flexibility and clear project goals significantly enhanced collaborative engagement. Results align with social constructivist and social interdependence theories, confirming PjBL's effectiveness in developing cooperation through social interaction within the Zone of Proximal Development. The findings extend existing literature by demonstrating specific cooperation development mechanisms while providing practical implementation strategies for elementary Civics Education aligned with the Pancasila Student Profile and Merdeka Curriculum frameworks.